A JIGSAW TYPE COOPERATIVE LEARNING MODEL ASSISTED BY STUDENT WORKSHEET INFLUENCE ON LEARNING OUTCOMES IN THE CHEMISTRY OF SALT HYDROLYSIS MATERIALS - Ariani, Baiq Istira Ariani; Burhanuddin; Lalu Rudyat Telly Savalas (UIN Mataram, 2023)
Despite its popularity, the discovery learning model is not always successful in improving learning outcomes, especially in populations of students with large ability disparities. The group of high achieving students is too dominant and the low achieving group tends to participate less, so they don't get optimal results. Therefore, alternative learning models are needed to encourage class participation. The purpose of this study was to identify the effect of the jigsaw type cooperative learning model using student worksheet on the results of learning chemistry on salt hydrolysis in class XI MIPA students. This research uses a non-equivalent control group design. The application of the jigsaw type cooperative model and discovery learning are used as independent variable and learning outcomes are designated as dependent variable. Samples were taken through the non-probability sampling technique with saturated sampling. Classes XI MIPA 1 and XI MIPA 2 are the experimental class and the control class in this study, respectively. Data collection using pre-test and post-test on the sample class with multiple choice test instruments. Hypothesis testing with the t-test to produce 3.48 and with a value of 2.01. This data shows that the jigsaw type cooperative model using student worksheet has a significant impact on student learning outcomes as indicated by Tcount which is greater than TTable .